The perils of reconstruction: the case of Proto-Yao - Benedict, Paul K. (2024)
From time to time the writer has informally expressed the view that it often proves easier to reconstruct at an earlier level, say Proto-Sino-Tibetan. than at a later level. say Proto-Sinitic (Chinese/ Bai). This has been described as an 'illusion' (Matisoff 1990: 1 17), but cases continue to surface that support the notion. It is even possible for a whole series of related components to be involved, as in a recent case that has come up involving the Miao-Yao (MY) family.